Analyzing the Impact of Capital Structure on Stock Returns: A Study of NEPSE-listed Companies - Jai Kumar Mahato (Research Parks Publishers, 2024)
This study delves into the intricate relationship between capital structure and stock returns, focusing on companies listed on the “Nepal Stock Exchange” (NEPSE) during the period from 2016 to 2020. Capital structure, a critical facet of financial management, entails the strategic mix of equity and debt employed to fund a company's operations. The study aims to contribute valuable insights to managerial decision-making and policymaking by investigating the implications of various capital structures on stock returns.Financial managers are tasked with striking a delicate balance between potential gains and losses while formulating the optimal capital structure. Debt, often considered a cost-effective alternative to equity financing, presents additional benefits such as tax deductions. The complexity of this decision-making process lies in the profound impact that the chosen capital structure can have on the overall worth of the company. Drawing on secondary data derived from the financial filings of NEPSE-listed companies, this research employs correlation and regression analyses to unravel the intricate dynamics between capital structure and stock returns.